2016
DOI: 10.1103/physreva.93.012325
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic cooling in liquid-state nuclear magnetic resonance

Abstract: Algorithmic cooling is a method that employs thermalization to increase qubit purification level, namely it reduces the qubit-system's entropy. We utilized gradient ascent pulse engineering (GRAPE), an optimal control algorithm, to implement algorithmic cooling in liquid state nuclear magnetic resonance. Various cooling algorithms were applied onto the three qubits of 13 C2-trichloroethylene, cooling the system beyond Shannon's entropy bound in several different ways. In particular, in one experiment a carbon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…One of the computational qubits operated as target qubit which is going to be cooled by applying PPA while other computational qubits play a role in entropy compression [33]. This cooling process can be implemented arXiv:1901.01166v1 [quant-ph] 4 Jan 2019 with a minimal system composed of just 3-qubit [32][33][34][35]. For the four-stroke engine, we consider the target qubit as the working fluid (see Fig.…”
Section: The Working Fluidmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the computational qubits operated as target qubit which is going to be cooled by applying PPA while other computational qubits play a role in entropy compression [33]. This cooling process can be implemented arXiv:1901.01166v1 [quant-ph] 4 Jan 2019 with a minimal system composed of just 3-qubit [32][33][34][35]. For the four-stroke engine, we consider the target qubit as the working fluid (see Fig.…”
Section: The Working Fluidmentioning
confidence: 99%
“…We used parameters of 13 C 2 -trichloroethylene (TCE) (see Table I) with paramagnetic reagent Cr(acac) 3 in cloroform-d solution (CDCl 3 ) in our numerical calculations, which are also experimentally used for HBAC in Refs. [34,35]. Carbon-1 and Carbon-2 qubits are classified as the target and the compression qubits.…”
Section: The Working Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Chang et al implemented cooling solely by the final compression gate on three fluorines in C 2 F 3 BR using LSNMR. Full implementation of HBAC in LSNMR was accomplished much later in [21].…”
Section: Experimental Algorithmic Cooling With Nmr Qipmentioning
confidence: 99%
“…Here, the reset qubits periodically release their excess entropy to a heat-bath so that higher cooling of the computation qubit can be achieved by constructive iterations of AC. Since then, several HBAC algorithms have been proposed [10][11][12][13][14] and numerous experimental studies have also been reported [15][16][17][18][19][20][21] which use three or five qubit entropy compression circuits as the building block for AC. More recently asymptotic bounds for HBAC algorithms have been estimated numerically by Raeisi et * mahesh.ts@iiserpune.ac.in al.…”
Section: Introductionmentioning
confidence: 99%